CGSC, Audit Quality, And Internet Reporting: The Mediation and Moderation Analysis - Mohamed S. El-Deeb; Yasser T. Halim; Ahmed F. Elbayoumi (Journal of Accounting and Management Information Systems (JAMIS), 2024)
Research Questions- In what ways does the corporate governance scorecard (CGSC) and internet reporting intersect with audit quality? To what extent do technological advancement and auditor qualifications moderate the association between internet reporting, corporate governance (CGSC), and audit quality? In what capacity does audit quality mediate the association between internet reporting and the corporate governance scorecard (CGSC)? Motivation- The rationale for conducting this study is to fill a known void in the academic literature concerning corporate governance in developing nations, with Egypt serving as an example. Idea- The main idea of our study is to understand the impact of CGSC-measured corporate governance on internet reporting of financial and non-financial information. Our study also seeks to determine whether audit quality acts as a mediator and whether auditor qualifications and technological advancement moderate this relationship. Data- Using a questionnaire, 258 auditors from various auditing firms, including the Big4 and national audit firms with international affiliation, data were collected. Tools- Factor analysis, Pearson correlation, and Structure Equation Modelling. Findings- Corporate governance assessed by CGSC improves the Internet reporting through the mediation of audit quality, with auditor qualifications and technological advancement serving as moderators. Contribution- This study contributes to the scholarly comprehension of the association that exist among CGSC, audit quality, and internet reporting. Implications for utilizing CGSC as a metric for evaluating corporate governance practices and its influence on online reporting are both theoretical and practical in nature. The investigation contributes valuable perspectives that can guide decision-making in practical and theoretical settings, thereby enhancing the academic discourse.
Keywords: M42; G34; 650; Corporate governance scorecard (CGSC); Audit quality; Auditor qualifications; Technological advancement; Internet reporting